Grounding moderate understanding of Islam through At-Taqwa mosque network, Cirebon City - Istiqomah Istiqomah; Septiani Resmalasari (Universitas Muhammadiyah Magelang, 2023)
There are many programs that have been initiated in order to foster tolerance values in society. One of the religious organizations is the manager or DKM of the mosque which plays a role in spreading moderate understanding. The purpose of this community service is to increase the capacity of the administrators of the At-Taqwa Mosque network in fostering an understanding of religious moderation. The method used in community service is the Participatory Rural Appraisal (PRA) approach. The workshop activities received a positive response from the participants and it was proven by the level of satisfaction of 82.4 points.